Quality assurance for care of the dying: engaging with clinical services to facilitate a regional cross-sectional survey of bereaved relatives' views - Catriona Mayland; Tamsin McGlinchey; Maureen Gambles; Helen Mulholland; John Ellershaw (BMC, 2018)
Abstract Background Globally, having the 'patient and /or family voice' engaged when measuring quality of care for the dying is fundamentally important. This is particularly pertinent within the United Kingdom, where changes to national guidance about care provided to dying patients has heightened the importance of quality assurance and user-feedback. Our main aim was to engage with clinical services (hospice, hospital and community settings) within a specific English region and conduct a bereaved relatives' cross-sectional survey about quality of care. Our secondary aim was to explore levers and barriers to project participation as perceived by organisational representatives. Methods Each organisation identified a consecutive sample of next-of-kin to adult patients who died between 1st September and 30th November 2014. Those who had an unexpected death or were involved in a formal complaint were excluded. The 'Care Of the Dying Evaluation' (CODE™) questionnaire was posted out three months following the bereavement. One-to-one interviews were undertaken with a purposive sample of organisational representatives to explore experiences about project participation. Results Of the 30 invited organisations, 18 were able to participate comprising: 7 hospitals, 7 hospices and 4 community settings. There were 1774 deaths which met the inclusion criteria but 460 (26%) were excluded due to inaccurate next-of-kin details. Subsequently, 1283 CODE™ questionnaires were sent out, with 354 completed (27% response rate). Overall, most participants perceived good quality of care. A notable minority reported poor care for symptom control and communication especially within the hospital. Nine interviews were conducted - levers to project participation included the 'significance of user-feedback and the opportunity to use results in a meaningful way'; the main barrier was related to 'concern about causing distress to bereaved relatives'. Conclusions Overall, being able to engage with 18 (60%) organisations within the region and conduct the bereaved relatives' survey showed success of this initiative and was supported by interview findings. The potential to be able to benchmark user-feedback against other organisations was thought to help focus on areas to develop services. This type of quality assurance project could form a template model and be replicated on a national and international level.